The role of Digital Public Relations in marketing of the banking services: An analytical study on banks in the Kingdom of Bahrain - Alrashed, Maha Sami (Journal of Humanities & Social Sciences, 2022)
This research paper aimed at identify the content of the social networks used by commercial and Islamic banks in the Kingdom of Bahrain to market their services as well as monitor the interaction indicators between the content of the official accounts of the study sample banks and their target audiences. The researcher relied on the descriptive survey method to analyze the content of the official accounts of commercial and Islamic banks in the Kingdom of Bahrain with sample selection being National Bank of Bahrain and Bahrain Islamic Bank to analyze the content of their official accounts on Twitter and Instagram from January 2021 to October 2021. The study concluded a set of results, the most important of which are: -The main types of content that banks use in marketing their services on Twitter is “news” with a rate of (69.1%), followed by “information” (27.3%). -The most common language used by banks in marketing their services on Twitter is the "language mixture", which was repeated by (49.9%), followed by "standard language (27.1%)" -The most common method of discourse that banks use in marketing their services on Twitter is ”promotional” with a percentage of (49.2%), followed by “informative” with a percentage of (45.2%).